PENGARUH FOOD TABOO, KONSUMSI TABLET FE DAN KAFEIN TEH TERHADAP NILAI KADAR HAEMOGLOBIN PADA IBU HAMIL - Akbarini, Oon Fatonah; Pramuwidya, Asmaurika; Lamana, Aspia (Jurnal Pendidikan Kesehatan (e-Journal), 2024)
Pregnancy anemia is a body condition with a hemoglobin level in the blood of <11 gr% in the 1st and 3rd trimesters or a hemoglobin level of <10.5% in the 2nd trimester. The incidence of anemia in pregnant women in the Antibar Community Health Center area, East Mempawah District, was 61 people in 2021. Anemia in pregnant women has impacts such as abortion, bleeding during pregnancy, premature birth, fetal disorders, labor process disorders, postpartum disorders, congenital defects, LBW, perinatal death and others. Based on preliminary results, there are still pregnant women who implement food taboos during their pregnancy. The level of compliance with iron tablet consumption among pregnant women in West Kalimantan Province is 82.50%). Currently, people in Mempawah Regency still have a culture of drinking tea in their daily lives, including pregnant women. The aim of this research is to analyze the effect of food taboo, consumption of fe tablets and tea caffeine on hemoglobin levels. This type of research is a quantitative study, with a cross sectional design. The population is all pregnant women, the sample for this study was 40 pregnant women. Data analysis used the Chi suare statistical test. The statistical test results show a p-value of 0.937, meaning there is no relationship between food taboo and hemoglobin levels, there is a relationship between consumption of Fe tablets and hemoglobin levels with a p-value of 0.021 and there is a relationship between the habit of drinking tea and hemoglobin levels with a p-value of 0.04. From these results, it is very important for pregnant women to pay more attention to their consumption patterns of drinking tea and Fe tablets so that there is no decrease in hemoglobin during pregnancy..